Wybuchowa aporia - Lipowiecki, Mark (Er(r)go. Teoria - Literatura - Kultura, 2015)
Mark Lipowiecki the University of Colorado at Boulder, USA. "An Explosive Aporia" The article traces and analyses the origin of Russian postmodernism, seeing it as a reaction to soviet meta-narratives and the official attempts to control the avant-garde movements. But the particular shape which post-modernism adopted in Russia is also reflecting deeper cultural dominants, notably the lack of a middle ground between various cultural extremes, which in turn appear to constitute the foundations of Russian culture. Russian post-modernism, the article argues, is thus characterised by a constant internal struggle between opposing discourses rather than by a consistent opposition to social and political traditions of modernity.